Dr. Tony Fauci [videorecording (DVD)] (PBS Distribution, 2024)
Follow Dr. Anthony Fauci as he grapples with the COVID-19 pandemic and his 50-year career as the Nation's leading public health advocate. Witness a rarely seen side of the physician, husband, and father as he confronts political backlash, a new administration, and questions of the future.